KEMUNGKINAN PENGGUNAAN BAHAN PENGAWET ZFK - Sasa Abdurrohim; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1996)
Since CCA preservative was banned  in Indonesia, alternative preservative should be searched.  One of  the preservative which  has good fixation characteristic like CCA is ZFE. preservative  that contain zink, fluor and chrom.The retention  and  penetration  of  ZFK  in five Indonesian  wood  species  were studied.   The ZFK preservative  was applied  using soaking  method for  3, 5 and 7 days, where the solution concentration  applied was 5 %  and 10%.  Five wood species  choosed  in the experiment were damar  (Agathis loranthifolia),  keruing (Dipterocarpus caudiferus), jelutung  (Dyera costulata), meranti merah (Shorea palembanica) and nyatoh (Palaquium leiocarpum).The lest results based on  retention and penetration  requirements for  wood used under roof, and in the open air both without ground contact, showed  that only two species,  keruing  and jelutung,    could satisfactorily  meet the standard  under the experimental conditions, while other tree species  (damar, meranti merah and nyatoh) do not comply with tire standard.  For under roof  and in the open air uses without ground  contact keruing can be consecutively soaked for 7 days in Basilit ZFK solution of 10% , while jelutung for 5 days.